Kritik Iqbal terhadap Argumen-Argumen Ketuhanan - Abi Akbar Atma (ILMU USHULUDDIN, 2015)
This article describes Allama Muhammad Iqbal’s criticism on three arguments of scholastic divinity which is considered to have weaknesses and flaws in verification of the existence of God. The scholastic argument is Ontology, Cosmology, and Teleology. Then Iqbal offered new arguments about existence of God, in which they consist of: 1) Intuitive Argument 2) God as the Eternal Beauty, Personal Absolute, and Spiritual Truth.